Phase transition-like behaviors of propagation of passenger stranding phenomena in subway networks - Xinyi Li; Shengda Zhao; Liang Wang; Qing Wang; Xun Zhang; Fang Liu; Xiaodong Zhang; Daqing Gong; Xinghua Zhang (npj Sustainable Mobility and Transport)
Abstract Subways are essential for urban commuting, particularly in large metropolitan areas. However, as cities expand, subways face increasing challenges in balancing passenger demand with available service, leading to passengers being stranded at stations. A key issue is that such stranding can propagate across multiple stations, forming clusters that significantly impact global service efficiency. This phenomenon, termed “propagation of passenger stranding (PPS)”, is studied based on a data-driven model. A transition point, determined by the shifting balance between supply and demand, dictates whether PPS will grow or diminish, serving as a threshold for subway service resilience. A nonlocal correlation pattern, key to PPS formation, is revealed using the eigen microstate method, alongside the local balance of demand and service and network topology. The findings reveal the resilience mechanism of service systems in networks where trains serve as the medium and identify key factors for enhancing resilience.